Optimization of RF 370 Type DC Motor System with LQR and LQT Method Approach in Community Service Program to Improve Linear Dynamics-Based Control System Performance - Mohammad Ryan Fauzi (Maritime in Community Service and Empowerment, 2024)
The application of DC motors is widely recognized due to their suitability for various control-based systems, particularly in industrial and community-driven applications. In community contexts, precise motor control systems are essential for improving productivity and system efficiency. This study focuses on optimizing the performance of the RF-370 DC motor using the Linear Quadratic Regulator (LQR) and Linear Quadratic Tracker (LQT) methods, which are well-known for their capability to design efficient and responsive control systems. DC motors play a pivotal role in both advanced technologies and industrial processes. Specific examples of their applications include spacecraft navigation, missile guidance, aircraft control systems, and satellite positioning. In industrial settings, DC motor control is critical for regulating production machines during operations, such as controlling pressure, temperature, flow, friction, and humidity. The growing demand for energy-efficient and high-performance systems has made optimal control a crucial area of research. Optimal control focuses on achieving a balance between performance objectives and technical constraints to create systems that operate efficiently within physical limitations. This involves designing controllers that minimize deviations from desired behaviors while maintaining system stability. The LQR method, for example, calculates optimal control actions by minimizing a defined cost function that balances control effort and system state deviations. Similarly, the LQT method enhances system performance by precisely tracking reference signals. This research highlights the potential of integrating LQR and LQT methodologies into community service initiatives. By applying these advanced control techniques to small-scale industries and educational training programs, the study demonstrates the practical benefits of improving local technological capacities and fostering innovation. The outcomes of this research are particularly relevant for communities seeking to adopt affordable and effective motor control solutions in sectors such as agriculture, creative industries, and vocational education.